On q-Quasi-Newton’s Method for Unconstrained Multiobjective Optimization Problems - Lai, Kin Keung; Mishra, Shashi Kant; Ram, Bhagwat (Mathematics (Basel), 2020)
A parameter-free optimization technique is applied in Quasi-Newton’s method for solving unconstrained multiobjective optimization problems. The components of the Hessian matrix are constructed using q-derivative, which is positive definite at every iteration. The step-length is computed by an Armijo-like rule which is responsible to escape the point from local minimum to global minimum at every iteration due to q-derivative. Further, the rate of convergence is proved as a superlinear in a local neighborhood of a minimum point based on q-derivative. Finally, the numerical experiments show better performance.